Hubungan Pengetahuan dan Sikap dengan Rendahnya Kunjungan Pekerja Ke Pos Usaha Kesehatan Kerja (UKK) - Gita Fajrianti (STIKes Surya Global Yogyakarta, 2021)
ABSTRACT Background of Study : UKK Posts is a forum for community-based health efforts for informal sector workers which is managed and organized from, by, for and with the working community through the provision of health services with promotive and preventive main approaches, accompanied by simple/limited curative and rehabilitative. Based on the Gerunggang Public Health Centre In 2019-2020, there was a decrease in visits from 100 members to 55 members. The purpose of this study was to determine the factors associated with low worker visits to the UKK Post in the Gerunggang Public Health Centre in 2021. Methods :This research uses a cross-sectional design carried out in the Gerunggang Public Health Centre. The population in this study were all members of the UKK Post in the Gerunggang Public Health Centre has 100 members. The research instrument used is a quantitative approach and interview methods as well as measuring tools through questionnaires. Results : The results showed that there was a significant relationship between Education with p value = 0.005, Knowledge with p value = 0.024, Attitude with p value = 0.020 on the low number of visits by workers to UKK Posts. There is no relationship between the role of cadres with a p value of 0.599. Conclusion : From the results of the study, it is recommended to increase the media for health education that is more interesting and educative. Collaborating with cross programs, Cadres can inform routine schedules and subsequent meetings. Keywords : Knowledge, Attitude, Low Worker, UKK